Pandemic effects on companies financial performance: evidence from Malaysia listed company / Fathirah Khairunnisa Saidul - Saidul, Fathirah Khairunnisa (2022)
This study aims to investigate the effects of pandemic on the companies financial performance in Malaysia and the data cover period from 2019 — 2020 which is 2 years. There have numerous elements that can have an impact on a company's financial performance as a result of a pandemic. The leverage ratio (DR), revenue, and growth (EPS) are the three key topics will become address in this study. The link between each independent variable and the dependent variable, profitability, which may be assess using return on assets, is examine using a multiple regression model in this study. The sample for this study was collected from the annual report throughout a four-year period, from 2019 to 2020. This study also aid analysts by allowing them to collect data in a more methodical manner. It also assists in predicting future performance between these companies, as this illness currently lacks a cure, and comparing which one performs better in the future. According to the findings of this study, liquidity, as measure by the leverage ratio, is the sole variable that will have a substantial impact on the return on asset and, as a result, on the financial performance of Malaysian enterprises.